2019
DOI: 10.1159/000503582
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Platelet Reactivity under Aspirin Medication and Major Adverse Cardiac and Cerebrovascular Events in Patients with Coronary Artery Disease

Abstract: Aspirin is indispensable in secondary prevention of ischemic events in patients with coronary artery disease (CAD). However, insufficient platelet inhibition despite aspirin medication is frequent. This is referred to as high on-treatment platelet reactivity (HTPR). Nevertheless, if this is associated with clinical outcome instead of only laboratory phenomenon remains unclear so far. In this study, we test whether patients with ischemic events have higher platelet reactivity despite aspirin medication than pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…12 Genotyping aspirin resistance, however, has gained attention, i.e., for the genetic polymorphism of the PTGS1 gene that encodes COX-1, as specific short nucleotide polymorphisms and haplotypes dysregulate arachidonic acidinduced thromboxane production leading to inadequate aspirin responses. 13 Aspirin HPR, a risk factor for major adverse cardiac events (MACE) after percutaneous coronary intervention (PCI), 14 is observed in up to 15% of patients undergoing neuroendovascular interventions; however, in alignment with cardiovascular studies, a consistent association of aspirin PR and clinical outcomes is not evident. However, two recent metaanalyses suggest that in DAPT, low-dose (150 mg daily) as compared to high-dose aspirin given either before or after the neuroendovascular intervention increases late (>6 months) thromboembolism by about 2.5 times without differences in hemorrhagic events.…”
Section: Resultsmentioning
confidence: 99%
“…12 Genotyping aspirin resistance, however, has gained attention, i.e., for the genetic polymorphism of the PTGS1 gene that encodes COX-1, as specific short nucleotide polymorphisms and haplotypes dysregulate arachidonic acidinduced thromboxane production leading to inadequate aspirin responses. 13 Aspirin HPR, a risk factor for major adverse cardiac events (MACE) after percutaneous coronary intervention (PCI), 14 is observed in up to 15% of patients undergoing neuroendovascular interventions; however, in alignment with cardiovascular studies, a consistent association of aspirin PR and clinical outcomes is not evident. However, two recent metaanalyses suggest that in DAPT, low-dose (150 mg daily) as compared to high-dose aspirin given either before or after the neuroendovascular intervention increases late (>6 months) thromboembolism by about 2.5 times without differences in hemorrhagic events.…”
Section: Resultsmentioning
confidence: 99%
“…However, this is not surprising as it has been shown that a primarily thrombocytopenia under MTX is followed by a phase of thrombocytosis [40]. Platelet reactivity is known to be associated with cardiovascular events [41]. Hence, this might have influenced outcome in a counterbalanced way after AMI as well.…”
Section: Discussionmentioning
confidence: 99%
“…Several possible causes were put forward to explain the phenomenon of ischemic events in patients on antiplatelet treatment, such as genetic polymorphisms, drugdrug interactions, or HTPR (Buonamici et al, 2007;Russo et al, 2016). HTPR observed during both ASA and P2Y 12 receptor antagonists therapy was associated with a higher risk of adverse cardiovascular events (Buonamici et al, 2007;Aradi et al, 2010;Dannenberg et al, 2020). As was previously described, miRNAs are able to modify the expression of platelet proteins by targeting mRNAs and thereby altering their biochemical pathways including those associated with drug response.…”
Section: Microrna Studies Linked With Antiplatelet Treatmentmentioning
confidence: 99%
“…It is worth noting that many factors may increase the risk of MACE, but the mechanisms of correlations between miRNAs, platelet reactivity, and MACE are not clear. The risk of cardiovascular events can be heightened due to a number of factors, i.e., HTPR (Buonamici et al, 2007;Aradi et al, 2010;Dannenberg et al, 2020). However, miRNAs might also influence the transcription of specific genes and lead to the abnormalities of the process of hemostasis, thrombosis, and antiplatelet drug response (Teruel-Montoya et al, 2015;Parker et al, 2020).…”
Section: Acs and Macementioning
confidence: 99%